Manajemen Kepala Sekolah Dalam Pengembangan Kompetensi Profesionalitas Guru di Smp MMT Mercubuana Tulang Bawang Barat - Hariyandi, Yogi; Budiyono, Apri Eka; Tamyiz, Ahmad (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to reveal how school management develops the professional competencies of teachers at SMP MMT Mercubuana Tulang Bawang Barat, focusing on two main issues: how planning is conducted and how the development is implemented. Teacher professional competence is an essential element in supporting the quality of education, thus requiring effective managerial leadership from the school principal. This study employs a descriptive qualitative approach, with data collection conducted through direct observation of the school conditions and teacher programs, in-depth interviews with the principal, vice principal, and selected teachers, as well as documentation from various school records and reports. The results indicate that in the planning stage, the principal formulates work programs based on an analysis of teachers' needs, performance evaluation results, and considerations of school policies and curriculum. These programs are developed through internal meetings and involve teacher participation. In terms of implementation, the principal coordinates activities such as training, routine mentoring, academic supervision, and providing opportunities for participation in professional development activities outside the school. This strategy is carried out continuously with a collaborative and humanistic approach. Challenges faced include budget limitations and uneven levels of teacher enthusiasm. However, these issues are addressed through intensive communication and personal motivation. Additionally, the principal strives to create an environment that supports teachers' professional development by recognizing achievements. The study concludes that the principal plays a crucial role in enhancing teacher professionalism through structured and participatory management. The development of teacher competencies is not only an individual responsibility but also a collaborative effort involving all elements within the school. It is hoped that this will contribute to the improvement of education quality at SMP MMT Mercubuana Tulang Bawang Barat.